Variasi Persentase Pati Resisten Jagung Tipe 3 pada Sifat Fisik dan Organoleptik Es Krim Kelapa - Susilo, Donor Utomo Muhammad; Amperawati, Suharyani; Imelda, Fenny (Politeknik Negeri Lhokseumawe, 2024)
The main ingredient of ice cream is cream. Regularly, ice cream is made from animal fat of milk, but can be made from vegetable fats as well. Coconut milk as a source of vegetable fat (cream) can be an alternative substance for making ice cream and is suitable for people with lactose intolerance. Making coconut ice cream requires a gelling agent dissolved in ice cream mixture (ICM). Corn starch that was modified physically (RS type 3) can be used in making of coconut ice cream which functions as a gelling agent. The research purpose was understanding of how to make coconut cream which can produce an overrun quality and organoleptic (hedonic) test. The study was conducted in a laboratory scale with a completely randomized design (CRD) with 4 variations in the proportion of the addition of this resistant starch and 3 replications which were tested for analysis of variant (ANOVA) and further tests with the Duncan and Kruskal Wallis multiple distance test. The results showed that the addition of resistant starch had an effect on the overrun significantly with the highest value of 23.53% at the 5% level of the proportion of ingredient. The hedonic test for the coconut ice creams at the proportion of ingredient was 5% as the highest score observed by the panelists whose the score was not significantly different from the proportions of the ingredients 3% and 6%.